Exploration of Social Values in the Novel Hafalan Shalat Delisa by Tere Liye: A Study in the Sociology of Literature - Frananda, Muhamad; Ahmad Rangga Prihadit (Universitas Swadaya Gunung Jati, 2025)
Researchers are interested in the novel Hafalan Shalat Delisa by Tere Liye because it tells the story of the tsunami natural disaster that hit Aceh in 2004. Apart from that, there are social values ​​contained in this novel which are interesting to study. This research aims to investigate and describe the social values ​​contained in the novel entitled Hafalan Shalat Delisa by Tere Liye. The method used in this research is descriptive qualitative. The approach used is a literary sociology approach. The data collection technique used was reading and note-taking. The data analysis technique applies the Miles & Humbermen concept. The results of this research are to describe social values ​​including; resilience in the face of tragedy, sacrifice and courage, spirituality/faith, and solidarity. The conclusion of this research is that the novel Hafalan Shalat Delisa by Tere Liye contains social values